Cisco: strategic alliances - who, when and why - Mitchell, William (Henry Stewart Talks, 2018)
This case study assesses the IT company Cisco and the reasons for its success over about two decades. It is argued that the leading cause of this success is Cisco’s extensive portfolio of ways in which it acquires new resources. These include: extensive R&D investment, almost 200 acquisitions between 1993 and 2007, and an extensive number of alliances managed by a competent alliance leadership team.